2006
DOI: 10.1002/bsl.679
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathy in adolescent female offenders: an item response theory analysis of the psychopathy checklist: youth version

Abstract: The present study examined the applicability of the PCL:YV items to a sample of detained adolescent girls. Item response theory (IRT) was used to analyze test and item functioning of the PCL:YV. Examination of IRT trace lines indicated that the items most discriminating of the underlying construct of psychopathy included "callousness and a lack of empathy", "conning and manipulation", and "a grandiose sense of self-worth". Results from the analyses also demonstrated that the items least discriminating in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 68 publications
3
49
1
1
Order By: Relevance
“…The psychopathy construct is believed to exist in male and female adults, moreover there is a controversial discussion about psychopathy in women, and the potential downward extension to girls [57]. The psychopathy checklist-revised (PCL-R) [34] used for adult female offenders found lower means and a lower prevalence of psychopathy in female prisoners than in incarcerated men [54,55,79].…”
Section: J Psychopathy Across Gendermentioning
confidence: 99%
“…The psychopathy construct is believed to exist in male and female adults, moreover there is a controversial discussion about psychopathy in women, and the potential downward extension to girls [57]. The psychopathy checklist-revised (PCL-R) [34] used for adult female offenders found lower means and a lower prevalence of psychopathy in female prisoners than in incarcerated men [54,55,79].…”
Section: J Psychopathy Across Gendermentioning
confidence: 99%
“…Boys had higher psychopathy scores as measured by the APSD. Schrum and Salekin (2006) examined the applicability of the PCL:YV items to a sample of detained adolescent girls. Item response theory (IRT) was used to analyze test and item functioning of the PCL:YV.…”
Section: Introductionmentioning
confidence: 99%
“…Krueger et al (2005) and Markon and Krueger (2005) also found superior fit for a latent trait model in a study of externalizing diagnoses in adulthood. In the adolescent literature, latent trait modeling of externalizing behaviors has revealed meaningful latent traits (Gelhorn et al 2009;Schrum and Salekin 2006;Van den Oord et al 2003), which supports a dimensional conceptualization. It should be noted that support for dimensional structures has even been found when modeling categorical symptoms and diagnoses (e.g., Gelhorn et al 2009;Krueger et al 2005;Markon and Krueger 2005).…”
Section: Discussionmentioning
confidence: 91%
“…The same has been found for latent trait modeling of general delinquency indicators (Van den Oord et al 2003). Finally, latent trait modeling of adolescent psychopathy (a personality style associated with callous affect, interpersonal manipulation, impulsivity, and delinquent behavior) has also provided support for a dimensional structure (Schrum and Salekin 2006).…”
Section: Structural Modeling Of Externalizing Psychopathology In Adolmentioning
confidence: 98%